LITERASI KEUANGAN, MOTIVASI, PREFERENSI RISIKO TERHADAP MINAT INVESTASI SAHAM MAHASISWA FEB UPN “VETERAN” JAWA TIMUR - Hanifah Qowiyamatin; Yuniningsih Yuniningsih (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Students as part of society become potential individuals to try investing This study aims to determine the effect of financial literacy, investment motivation, and risk preference on stock investment interest of students of the Faculty of Economics and Business Pembangunan Nasional “Veteran” Jawa Timur University. Collected data by distributing questionnaries to 110 active undergraduate students of the Economics and Business Pembangunan Nasional “Veteran” Jawa Timur University using the purposive sampling method with predetermined criteria. Partial Least Square (PLS) is used as the analysis method of this research. The result showed that there was no effect of financial literacy on interest in stock investment. However, motivation and risk preferences show a significant positive effect on interest in stock investment. Keywords: investment interest, financial literacy, investment motivation, risk preferences.